1987
DOI: 10.1172/jci113073
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and secretion of human colonic mucin glycoproteins.

Abstract: Synthesis and secretion of colonic mucin glycoprotein species were assessed during in vitro culture of colonic mucosal explants. DEAE-cellulose chromatography of endogenously labeled mucin glycoproteins from explant tissue demonstrated the presence of six mucin species (I-VI) similar to those identified earlier in surgical specimens of human colonic tissue. The relative proportions of mucin species I-VI in tissue explants remained constant throughout a 30-h culture period. However, the proportional representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…These findings are similar to those previously reported in ulcerative colitis using incorporation of radiolabelled glucosamine rather than N-acetylglucosamine. These studies showed reduced [4] or normal [22] incorporation in inactive ulcerative colitis but increased incorporation in active ulcerative colitis [5], Glucosamine incorporation by Crohn's disease explants has however previously been reported to be normal [4].…”
Section: Discussionmentioning
confidence: 91%
“…These findings are similar to those previously reported in ulcerative colitis using incorporation of radiolabelled glucosamine rather than N-acetylglucosamine. These studies showed reduced [4] or normal [22] incorporation in inactive ulcerative colitis but increased incorporation in active ulcerative colitis [5], Glucosamine incorporation by Crohn's disease explants has however previously been reported to be normal [4].…”
Section: Discussionmentioning
confidence: 91%
“…Smith and Podolsky 14 reported that incorporation of radiolabeled precursors into mucin glycoproteins was somewhat increased in ulcerative colitis explant tissue of the sigmoid colon, whereas, according to Tytgat, 7 MUC2 precursor synthesis was significantly decreased in a group with active ulcerative colitis, compared with findings in the group with ulcerative colitis in remission, as well as in normal controls. Our previous study revealed that DSS induced goblet cell depletion in the distal side of the colon, resulting in the contraction of colon length after 7 days of treatment with DSS.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis of coeliac disease was based on the presence of serum antibodies to endomysium, histological changes in small intestinal biopsy and other criteria as previously described [30]. Distal duodenal biopsies were fixed in 0·9% NaCl containing 10% formalin and paraffin embedded serial sections were used for morphological studies [29,31] and immunohistochemistry using rabbit anti‐human ITF antibody [15], polyclonal antibody to human colonic mucin [32,33], or pre‐immune serum. Xylene‐dewaxed and alcohol rehydrated paraffin sections were heated in a microwave with 0·01 m trisodium citrate solution.…”
Section: Methodsmentioning
confidence: 99%